INOVASI BAHAN AJAR ETNOMATEMATIKA MELALUI PERMAINAN ENGKLEK DENGAN GAME BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK - Adi Satrio Ardiansyah; Muhammad Anwar; Berlian Disi Prasetya; Rahmawati Kusuma Wardani; Nanik Ratnawati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to develop ethnomathematics teaching materials through engklek with game-based learning on students’ creative thinking skills. Research and development using the ADDIE model which is modified into ADD (Analysis, Design, dan Develop) was carried out with data collection techniques were observation, questionnaires, and documentation, while the data analysis techniques were descriptive analysis. Based on the results of the study, it was concluded that the feasibility score was 84.5% in the feasible category, the readability score was 81.5% in the very easy to understand category, and the student response score was 79% in the positive category. This study concludes that ethnomathematics teaching materials through engklek with game-based learning on students' creative thinking abilities are appropriate to be used as a medium for learning mathematics for students at the SMP/MTs level. The suggestions in this study are to develop better teaching materials and test their implementation on a wider scope in future research